ANALISIS KEMAMPUAN LITERASI MEMBACA SISWA KELAS V SEKOLAH DASAR - Eis Masfiroh; Seni Apriliya; Dwi Alia (Universitas Negeri Medan, 2025)
Abstract: This study is a qualitative study that aims to describe the reading literacy skills of fifth grade students in an elementary school in Cimanggu District in three aspects, namely the aspect of finding information, the aspect of interpreting and integrating, and the aspect of evaluating and reflecting on the contents of the reading. The subjects in this study were fifth grade students, with data collection techniques in the form of tests on 21 students, and interviews. Interviews were conducted using purposive sampling. Data analysis techniques were carried out through the stages of data reduction, data presentation, and drawing conclusions. This study shows that the reading literacy skills of fifth grade students vary in each aspect. Most students are able to find written information well, but still have difficulty in interpreting, integrating, and reflecting on the contents of the reading. The ability to evaluate and reflect on the contents of the reading is the weakest aspect, especially for students with sufficient and lacking categories. Keyword: Ability, Literacy, Reading Abstrak: Penelitian ini merupakan penelitian kualitatif yang bertujuan untuk mendeskripsikan kemampuan literasi membaca siswa kelas V di salah satu sekolah dasar di Kecamatan Cimanggu dalam tiga aspek yakni aspek menemukan informasi, aspek menginterpretasi dan mengintegrasikan serta aspek mengevaluasi dan merefleksi isi bacaan. Subjek dalam penelitian ini adalah siswa kelas V, dengan teknik pengumpulan data berupa tes kepada 21 siswa, dan wawancara. Wawancara dilakukan menggunakan purposive sampling. Teknik analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini menunjukkan bahwa kemampuan literasi membaca siswa kelas V bervariasi pada tiap aspeknya. Sebagian besar siswa mampu menemukan informasi tersurat dengan baik, namun masih kesulitan dalam menginterpretasi dan mengintegrasikan serta merefleksikan isi bacaan. Kemampuan mengevaluasi dan merefleksikan isi bacaan menjadi aspek yang paling lemah, terutama pada siswa dengan kategori cukup dan kurang. Kata Kunci: Kemampuan, Literasi, Membaca